Penerapan Teknik Data Mining Dengan Menggunakan Algoritma Eclat Untuk Mendukung Startegi Promosi - Dhea Rulana Arfasyah P; Dodi Siregar; Yunita Sari Siregar (SEMINAR NASIONAL TEKNOLOGI INFORMASI & KOMUNIKASI, 2021)
Business competition, especially in supermarkets and retail stores, forces shoppers to decide and find the best policy they want, especially in terms of convenience in choosing products. The problem faced by companies, especially customers or buyers, is that they cannot take full advantage of obtaining business information in terms of getting product locations easily and can save time. so the company database can not be used to support business decisions. This research requires a simple model that allows to determine the model when placing a product to overcome the problems that arise at this time by using data mining techniques in determining the product to be placed in a strategic place. products and can form this transaction pattern to find out information from products that often appear and is the process needed to change unused data points to provide more useful and valuable information to support decision making. This research produces a web-based system to be used in determining the items that must always be available according to the results of the eclat algorithm. The purpose of this study is to obtain an accurate pattern of transaction tendencies by applying the ECLAT Algorithm calculations and developing a varied search for case studies in minimarkets to find out patterns of shopping behavior based on consumer history using the ECLAT algorithm.